Insect Pests of Yard Long Bean (Vigna unguiculata subsp. sesquipedalis L.) in Major Growing Areas of Bangladesh (The Agriculturists, 2014)
The survey was conducted in intensive yard long bean growing areas such as Jessore, Dhaka, Narsingdi, Comilla and Chittagong of Bangladesh to know the pest incidence and their level of infestation on yard long bean during March to October 2009. The study comprised of 75 sample farmers through intensive field visit for field data collection and inspection. Pest complex of yard long bean and their intensity of incidence were more or less similar in five surveyed areas and there were at least nine out of ten insect pests at different growth stages in each sample area, which were aphid, pod borer, thrips, red mite, leaf miner, leaf beetle, green sting-bug, jute hairy caterpillar, hooded hopper and semilooperin descending order. It was revealed that aphid and pod borer were the major insect pests in the study areas. They were found to severely infest in yard long beans. Semilooper caused minor damage which occurred only in Jessore, Chandina and Mirshawrai sample areas. DOI: http://dx.doi.org/10.3329/agric.v11i2.17489 The Agriculturists 2013; 11(2) 66-73